Pleural Amebiasis Mimicking Pleural Effusion: A Case Report - Sari Handayani Utami; Irvan Medison; Dewi Wahyu Fitrina; Dessy Mizarti (HM Publisher, 2025)
Background: Pleural amebiasis is a rare manifestation of extraintestinal amebiasis, primarily occurring due to the rupture of an amebic liver abscess into the pleural space. We present an unusual case of pleural amebiasis in an elderly woman without any evidence of liver involvement. Case presentation: A 78-year-old female presented with a two-month history of progressive dyspnea, cough, and right-sided chest pain. She had a history of consuming raw vegetables. Examination revealed right-sided pleural effusion, which was confirmed by chest radiography and thoracic ultrasound. Pleural fluid analysis showed exudative effusion and microscopic examination demonstrated the presence of Entamoeba histolytica trophozoites. Despite the absence of a liver abscess on abdominal ultrasound, the patient was diagnosed with pleural amebiasis based on the pleural fluid findings. She was successfully treated with metronidazole and drainage of the pleural fluid. Conclusion: This case highlights the importance of considering pleural amebiasis as a differential diagnosis in patients with pleural effusion, even in the absence of liver involvement. Early diagnosis and prompt treatment with metronidazole and drainage are crucial for a favorable outcome.